The combination of water extracts of Curcumae Radix and Syzygii Flos improves benign prostatic hyperplasia by suppressing testosterone-induced proliferation of prostate cells in vivo and in vitro - Park, Ja Yeon; Park, Woo Yong; Lee, Beomsu; Song, Gahee; Jung, Yunu; Kwak, Hyun Jeong; Ahn, Kwang Seok; Park, Jinbong; Um, Jae-Young (Nutrition research and practice, 2025)
The traditional medicinal use of Radix (CR) and Flos (SF) supports the possible application in prostate-related diseases. In this study, we studied the therapeutic effects of CR and SF on benign prostatic hyperplasia (BPH) focusing on the proliferation of prostate cells. We established BPH mimicking and models to confirm the BPH-improving effects of CR and SF. The human prostate epithelial cell RWPE-1 and myofibroblast stromal cell WPMY-1 were treated 0.5 µM of testosterone propionate (TP) to induce cell proliferation. Also, BPH was induced by a 2-week-pretreatment with daily subcutaneous injections of TP (5 mg/kg/day) in the inguinal region of rats. Then, the TP-injected rats were divided into 5 groups as following: a BPH group (TP with corn oil), a CR group (TP with CR, 50 mg/kg/day), an SF group (TP with SF, 50 mg/kg/day), a CR+SF group (TP with the combination of CR and SF (CR+SF), 50 mg/kg/day), and a finasteride (Fi) group (TP with Fi, 1mg/kg/day). All treatments were carried out for 4 weeks following the pre-2-week period. TP treatments induced several pathological symptoms of BPH, such as enlarged prostate tissue, increased dihydrotestosterone serum level, and thickened epithelial thickness in TP-induced BPH rats. CR and SF treatment significantly alleviated these signs. In addition, CR and SF reduced the protein expression of BPH-related factors and cell proliferation. Similar patterns of changes were also seen models. Interestingly, the number of sperms decreased in Fi group, while in the CR+SF group, there was no reduction in sperm counts. These results showed that CR and SF alleviated BPH by inhibiting cell proliferation. Also, unlike Fi, sperm loss did not occur by CR and SF co-treatment. Based on these results, we suggested that CR and SF are new substitutes for BPH treatment.